An Analysis Of Students’ Interest In Learning English Through Pop Up Book Media - Alfin Fitrotul Aini; Selamet Riadi Jaelani; Ahmad Yusri; Muhammad Adib Nazri (Lembaga Pengembangan Kinerja Dosen, 2023)
This researcher aims to determine the students' interest through pop up books towards the success of English learning and the students' ability to use this technique in the learning process. For qualitative data, a questionnaire was used by distributing questionnaires to students and then conducting several interviews about the application of the technique. The test results increased to 85%. Meanwhile, as a result of analyzing students' opinions, we found that pop up book media is effective in improving students' English interest. Applying pop up technique in English learning, especially interest, is an appropriate strategy to increase students' English interest in the classroom.